2014
DOI: 10.3109/13880209.2014.948636
|View full text |Cite
|
Sign up to set email alerts
|

Immunological changes in the intestines and skin after senna administration

Abstract: Context: It has been reported that chronic sennoside use is associated with the development of melanosis coli, colonic adenoma, and/or carcinomas. Objectives: In this study, we investigated the immunological changes in the colon and skin after the administration of senna. Materials and methods: In this study, we investigated the colon and epidermis of C57/BL6j mice after a single administration of 10 mg/kg of senna [Cassia angustifolia (Caesalpiniaceae); 3, 6, 12, and 24 h after administration] and after repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Also, a prospective study suggested that the use of non‐fiber laxative increased the risk of CRC 23 . Animal studies also revealed that repeated administration of anthraquinone laxatives impaired intestinal peristalsis and promoted adenomatous hyperplasia of the colon 24,25 . In this study, we found that MC was not significantly associated with the histological progression of polyps.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Also, a prospective study suggested that the use of non‐fiber laxative increased the risk of CRC 23 . Animal studies also revealed that repeated administration of anthraquinone laxatives impaired intestinal peristalsis and promoted adenomatous hyperplasia of the colon 24,25 . In this study, we found that MC was not significantly associated with the histological progression of polyps.…”
Section: Discussionmentioning
confidence: 43%
“…23 Animal studies also revealed that repeated administration of anthraquinone laxatives impaired intestinal peristalsis and promoted adenomatous hyperplasia of the colon. 24,25 In this study, we found that MC was not significantly associated with the histological progression of polyps. The association of constipation, anthraquinone laxatives, and CRC should be noted.…”
Section: Discussionmentioning
confidence: 50%
“…Seven-week-old hairless Hos:HR-1 mice were obtained from Japan SLC, Inc. (Shizuoka, Japan) and housed in stainless steel wire mesh-bottomed cages with a constant temperature of 23℃±1℃, relative humidity of 50%±10%, and 12-hour light and dark cycles, as described previously3. Mice were provided laboratory chow and water ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study revealed that mast cells and 3,4 dihydroxyphenylalanine-positive cells in the colon were increased after repeated administration of senna. Further, in skin, the number of Langerhans cells decreased by repeated senna administration3. The skin barrier function plays an important role in protecting against the penetration of microbial pathogens and allergens, and against excessive transepidermal water loss (TEWL)4.…”
Section: Introductionmentioning
confidence: 99%
“…Research indicated that higher laxative doses result in a more severe grade of MC, de ned by the number of apoptotic bodies in colonic mucosa [6]. Based on the nding that repeated anthranoid administration induced impaired intestinal peristalsis as the number of senna administrations increased [10], a tendency toward an increased severity of MC was noted in an animal model. Thus, clinically relevant involvement of the severity of MC in humans has also been implied.…”
Section: Introductionmentioning
confidence: 99%